Application of Somatostatin, Chemotherapy Combined with TAE in Heterogeneous Glucagonoma Presented with Necrolytic Migratory Erythema - Shen, Chaoyong (Onco Targets Ther, 2019)
Glucagonoma, a rare neuroendocrine tumor of the pancreas, which is often misdiagnosed because of non-characteristic clinical manifestations. In addition, the treatment has not been well established for this disease so far. We here report a case of glucagonoma previous misdiagnosed as recurrent erythema. In this case, necrolytic migratory erythema was the main clinical manifestation, and he received surgical resection after admission although with liver metastasis. Postoperative pathological results showed that the heterogeneity of proliferative index in primary (Ki-67: 5~10%) and metastatic (Ki-67: 25~30%) tumors were obviously observed. One month postoperatively, abdominal CT and MRI showed multiple liver metastasis (type III) again. Interestingly, the skin rash was obviously improved after treatment with somatostatin combined with chemotherapy (octreotide, temozolomide and capecitabine). Subsequently, the patient received transarterial embolization (TAE). Up to now, no progression was noted for liver metastasis. Due to its rarity, clinical diagnosis is challenging; thus, further understanding of the disease by clinicians is helpful for early diagnosis and treatment, so as to improve the prognosis of patients.